2016
DOI: 10.17267/2317-3378rec.v5i2.1041
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculose: Adesão Ao Tratamento E Os Fatores Que Desencadeiam Em Abandono.

Abstract: A tuberculose é uma doença infectocontagiosa, que se caracteriza como uma emergência mundial. O tratamento dessa doença no Brasil é oferecido pelo Sistema Único de Saúde gratuitamente. O abandono do tratamento é um dos aspectos que mais repercutem no aumento dos índices de mortalidade, incidência e aumento da resistência às drogas. Conhecer os fatores de adesão e abandono do tratamento da tuberculose pode guiar práticas de saúde no controle da doença. Objetivo: Descrever fatores de adesão e abandono do tratame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
2
0
4
Order By: Relevance
“…The low schooling showed association with the outcome, a similar result to the writings of Arruda 14 , Harling et al 16 , and Viana, Redner and Ramos 19 . Possible explanations refer to the fact that the patient with lower school level often cannot understand what is prescribed or the health professional does not try to convey the information in a less formal way, leading to disinterest and consequent abandonment 23 . Communication between professionals and patients is of fundamental importance to avoid treatment abandonment and maintain regular attendance at the health unit.…”
Section: Discussion|mentioning
confidence: 99%
“…The low schooling showed association with the outcome, a similar result to the writings of Arruda 14 , Harling et al 16 , and Viana, Redner and Ramos 19 . Possible explanations refer to the fact that the patient with lower school level often cannot understand what is prescribed or the health professional does not try to convey the information in a less formal way, leading to disinterest and consequent abandonment 23 . Communication between professionals and patients is of fundamental importance to avoid treatment abandonment and maintain regular attendance at the health unit.…”
Section: Discussion|mentioning
confidence: 99%
“…Low education is one of the factors most associated with the incidence of TB in the population, due to the precariousness of life and lack of access to information. Low education can negatively influence the understanding of the importance of correct treatment and the risks of abandoning anti-TB therapy 21,22 . As in the study by Macedo et al 19 , we found that about one third of patients with TB had a low educational level.…”
Section: Discussionmentioning
confidence: 99%
“…e-Acadêmica, v. 4, n. 1, e2441436, 2023 (CC BY 4.0) | ISSN 2675-8539 | DOI: http://dx.doi.org/10.52076/eacad-v4i1.436 2 declarou a tuberculose uma emergência mundial, assim sendo implementados várias ações para o combate da doença (Santos Jr et al, 2016).…”
unclassified